A Stylistic and Analytical Study of Aesthetic Eloquence in the Meccan Verses: Surah Ad-Duḥā as a Model - Azhar Amir Zaen; Fara Diva Azizah; Zila Gustita; Desyoni Advensia (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study aims to examine the beauty of rhetorical style in the Makkiyah verses, focusing specifically on Surah Adh-Dhuha through the lens of balaghah, including the branches of ma‘ani, bayan, and badi’. The significance of this research lies in the way Surah Adh-Dhuha employs powerful rhetorical techniques to convey inner peace and divine reassurance to the Prophet Muhammad (ṣallallāhu ‘alaihi wasallam) during the early stage of his prophethood. Surah Adh-Dhuha was selected because of its strong emotional tone, aesthetic richness, and its role in comforting the Prophet during periods of distress. This study employs a descriptive qualitative method using textual analysis. The research process involved close reading and linguistic examination of the verses to uncover the layered rhetorical structures embedded in the surah. The findings reveal several rhetorical devices—such as tashbih, isti‘arah, tibaq, jinās, repetition, and muraṣṣa‘—that enhance both the spiritual and communicative power of the message. The surah also presents values of resilience and psychological reinforcement that remain relevant in contemporary contexts. The novelty of this research lies in its combined use of classical balaghah and modern stylistic perspectives to provide a more integrated analysis of Surah Adh-Dhuha, an approach that has not been extensively applied in previous studies. This study reaffirms the Qur’an’s status as an unparalleled linguistic and spiritual miracle, demonstrating how divine speech engages human emotion with exceptional eloquence and depth.